Long term preservation of motion with artificial cervical disc implants: A comparison between cervical disc replacement and rigid fusion with cage - Cincu, Rafael; Lorente, Francisco; Gomez, Joaquin; Eiras, Jose; Agrawal, Amit (Asian Journal of Neurosurgery, 2014)
Background: With the advancement of technologies there is more interest in the maintenance of the spine's biomechanical properties focusing on the preservation of the functional motion segment. In present article we describe our experience with 25 cases managed with artificial cervical discs with 28 Solis cage following cervical discectomy with a mean follow-up period of 7.5 year. Materials and Methods: All surgeries were performed by single surgeon from March 2004 to June 2005 with a follow-up till date. Patients with symptomatic single or multiple level diseases that had no prior cervical surgery were candidates for the study. Cohort demographics were comparable. Standardized clinical outcome measures and radiographic examinations were used at prescribed post-operative intervals to compare the treatment groups. Relief in radicular pain, cervical spine motion, and degenerative changes at follow-up were noted. Results: In a total 53 cases, the mean age in prosthesis group was 47 years (age range: 30-63 years) and mean age in cage group was 44 years (32-62 years). Mean hospital stay was 2.7 days in both the groups. At 4 weeks complete cervical movements could be achieved in 19 cases in artificial disc group. Maintenance of movement after 7.5 years was in 76% of these patients. Lordosis was maintained in all cases till date. There was no mortality or wound infection in our series. Conclusions: We conclude that artificial cervical disc could be an alternative to fixed spinal fusion as it represents the most physiological substitute of disc. However, there is need for further studies to support the use of artificial cervical disc prosthesis.
Keywords: Arthrodesis; cervical disc herniation; cervical arthroplasty; cervical prosthesis; prosthesis; spondylosis